2021
DOI: 10.1002/jsf2.20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of red pigments derived from Monascus purpureus: A comparison to industrial red pigments

Abstract: Background In recent years, the various advantages of fungal pigments over other natural or synthetic pigments have opened new avenues for wide range of applications in different industries. This study aims to determine the antimicrobial activity of fungal pigment produced by Monascus purpureus CMU001, against some Gr(+) and Gr(−) bacteria, yeasts and molds. Method In this study, the 96‐well microplate dilution and macro dilution methods were used to determine the minimum inhibitory concentration (MIC) values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Purpureusone is a known antifungal pigmented metabolite that is found in M. purpureus, as identified by [22], and inhibits the growth of Candida albicans and Streptomyces cerevisiae. Furthermore, the antibacterial and antifungal activity of the Monascus purpureus colourant is similar to ones reported [21,23]. The antibacterial activity of the colourant isolated from M. purpureus has received less attention than the antimicrobial activity of fungal fermented rice powder or Monascus koji powder.…”
Section: Mrsa Zhj(in Mm)supporting
confidence: 78%
“…Purpureusone is a known antifungal pigmented metabolite that is found in M. purpureus, as identified by [22], and inhibits the growth of Candida albicans and Streptomyces cerevisiae. Furthermore, the antibacterial and antifungal activity of the Monascus purpureus colourant is similar to ones reported [21,23]. The antibacterial activity of the colourant isolated from M. purpureus has received less attention than the antimicrobial activity of fungal fermented rice powder or Monascus koji powder.…”
Section: Mrsa Zhj(in Mm)supporting
confidence: 78%
“…These bioactive molecules play an important role in ameliorating metabolic disorders (Chen et al, 2022). Even though Monascus pigment's antimicrobial activities have been described, most of the studies were correlated to the anti-bacterial activities (Gökmen et al, 2021). Few studies on the antifungal activity of Monascus pigment against Candida albicans and Saccharomyces cerevisiae were reported (Cheng et al, 2011) and multicellular fungi (Kim et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies on the antifungal activity of Monascus pigment against Candida albicans and Saccharomyces cerevisiae were reported (Cheng et al, 2011) and multicellular fungi (Kim et al, 2006). The reported antifungal activity of M. purpureus is limited to mostly unicellular fungi/yeast, and in some studies, the antifungal activity of Monascus pigment against Aspergillus niger and Penicillium nigricans was not determined (Gökmen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The plates were incubated in the temperature of 37 ºC, and after 24 h and were examined for growth. The rst plate of concentrations cultured from the cell extract in which no colony was observed was considered as the MBC (19).…”
Section: Minimum Inhibitory Concentration (Mic) and Minimum Bacterici...mentioning
confidence: 99%
“…According to a study, the antibacterial activity of the Monascus pigment was found to be higher than that of the commercial red pigment against all tested bacteria. The MBC for Bacillus cereus ATCC11778 was determined to be 256 mg/ml for the commercial pigment, while it was lower at 128 mg/ml for the Monascus pigment (19). It is worth noting that Gram-negative bacteria, including E. coli, have a complex cell membrane structure consisting of lipopolysaccharides and two layers of phospholipids.…”
Section: Comparative Tests Of Pigment Antimicrobial Effectmentioning
confidence: 99%